2014
DOI: 10.1063/1.4900946
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimizing of the random atomic spin gyroscope drift based on the atomic spin gyroscope

Abstract: In order to improve the atom spin gyroscope's operational accuracy and compensate the random error caused by the nonlinear and weak-stability characteristic of the random atomic spin gyroscope (ASG) drift, the hybrid random drift error model based on autoregressive (AR) and genetic programming (GP) + genetic algorithm (GA) technique is established. The time series of random ASG drift is taken as the study object. The time series of random ASG drift is acquired by analyzing and preprocessing the measured data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…If the noises above are optimized by technology means, the sensitivity of the hybrid optical pumping SERF atomic magnetometer approaches to the ultimate sensitivity, which is also helpful to study the atomic spin gyroscope [48][49][50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…If the noises above are optimized by technology means, the sensitivity of the hybrid optical pumping SERF atomic magnetometer approaches to the ultimate sensitivity, which is also helpful to study the atomic spin gyroscope [48][49][50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…The MGGP algorithm performs well very on mixed, combinatorial, and many other complex problems. Moreover, the probability of falling into a local optimum is less than for the gradient search method [20]. The MGGP combines the GP ability to select the best model structure with the classical regression ability to estimate the parameter by using a multigene [26].…”
Section: B Mggp Model Of Magnetometer Noise 1) the Mggp Algorithmmentioning
confidence: 99%
“…For instance, any form of objective functions and constraints, whether linear or nonlinear, discrete or continuous can be processed by GP, in addition, it is very effective for global search. In [20], it was reported that GP could be applied in modeling and optimization of a random atomic spin gyroscope drift. In addition, in [21] the GP was utilized to lock the distributed feedback laser diode frequency to the gas absorption lines.…”
mentioning
confidence: 99%
“…17 First, GA can establish a model based on experimental data without any prior knowledge on the form of the model. 18 Second, no matter what form of the model takes, extremely accurate mathematical functions containing the inputs and outputs can be obtained with GA. 18 Third, a good model can be acquired with a small amount of data. Until now, GA has rarely been used in laser research.…”
Section: Introductionmentioning
confidence: 99%